2010
DOI: 10.1083/jcb.200908086
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride inhibits macropinocytosis by lowering submembranous pH and preventing Rac1 and Cdc42 signaling

Abstract: Inhibitors of Na+/H+ exchange proteins block macropinocytosis by lowering the pH near the plasma membrane, which in turn inhibits actin remodeling by Rho family GTPases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
543
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 755 publications
(564 citation statements)
references
References 82 publications
17
543
4
Order By: Relevance
“…Ecliptic pHluorin has a pK a of $7.1 and fluorescence also increases with increasing pH at 410 nm excitation; however, its emission spectrum does not have an isosbestic point to normalize intensity to protein abundance. In more recent studies, this limitation has been addressed by fusing ecliptic pHluorin and pH-insensitive mCherry (Koivusalo et al, 2010). This construct is easy to use with most fluorescence microscopes because ratiometric images can be obtained with GFP and mCherry filter sets, while filter sets for ratiometric pHluorin are distinct.…”
Section: Genetically Encoded Ph Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecliptic pHluorin has a pK a of $7.1 and fluorescence also increases with increasing pH at 410 nm excitation; however, its emission spectrum does not have an isosbestic point to normalize intensity to protein abundance. In more recent studies, this limitation has been addressed by fusing ecliptic pHluorin and pH-insensitive mCherry (Koivusalo et al, 2010). This construct is easy to use with most fluorescence microscopes because ratiometric images can be obtained with GFP and mCherry filter sets, while filter sets for ratiometric pHluorin are distinct.…”
Section: Genetically Encoded Ph Sensorsmentioning
confidence: 99%
“…23.2C; Choi, Webb, Chimenti, Jacobson, & Barber, 2013;Miesenböck et al, 1998) reveals an increase of focal adhesion pH during cell migration of mammalian cells. Further, targeting mCherry-pHluorin to the membrane by fusing the probe to the membrane-targeting sequence of Lyn demonstrated that changes in pH during macropinocytic lamellipodia extension are more profound in the immediate vicinity of the membrane (Koivusalo et al, 2010).…”
Section: Subcellular Ph Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we assessed the internalization mechanisms of pep- 15) Therefore, in order to confirm the internalization pathway of peptide 8, the cells were incubated with the tested peptides in the presence of several endocytosis inhibitors (amiloride, 16) an inhibitor of macropinocytosis; nystatin, 17) an inhibitor of caveolae-mediated endocytosis; and sucrose, 18) an inhibitor of clathrin-mediated endocytosis), and the intracellular uptake was measured by flow cytometry (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…4E). Therefore, we used the Rac1 blocker amiloride (Koivusalo et al, 2010) to assess whether Rac1 inhibition can change the effect of reggie-1 knockdown on FAs. The number of FAs in shR1 cells (but not in shLuc cells) was reduced to near normal, when cells were treated for 1 h with amiloride (Fig.…”
Section: Role Of Rac1 Activationmentioning
confidence: 99%